2015
DOI: 10.3945/ajcn.114.092262
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoleic acid is elevated in fatty liver disease and reflects hepatic lipogenesis

Abstract: The current data provide support for the use of the VLDL-triacylglycerol 16:1n-7 molar percentage as a biomarker for elevated liver fat when isotope use is not feasible; however, larger-scale confirmatory studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
4
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 62 publications
12
119
4
5
Order By: Relevance
“…Plasma (% total FA) PM +ly associated to MetS [65] Overweight adults (n = 24), elevated de novo lipogenesis and liver fat (VLDL)-triacylglycerols (mol% total FA) PM +ly associated with de novo lipogenesis, liver fat, and insulin resistance [63] Women's Health Initiative Memory Study (n = 6379), 11 years followup (n = 703), type-2 diabetes RBC membrane (% total FA) PM +ly associated with type-2 diabetes [64] Men and women (n = 358), aged 30-65 at coronary artery disease risk NEFA (μmol L −1 ) P M +ly association with NAFLD but not with atherosclerosis PM, palmitoleic acid; FFA, free fatty acids; TG, triacylglycerol; RBC, red blood cells; MetS, metabolic syndrome; CHD, coronary heart disease; NAFLD, nonalcoholic fatty liver disease, NASH, non-alcoholic steatohepatitis.…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Plasma (% total FA) PM +ly associated to MetS [65] Overweight adults (n = 24), elevated de novo lipogenesis and liver fat (VLDL)-triacylglycerols (mol% total FA) PM +ly associated with de novo lipogenesis, liver fat, and insulin resistance [63] Women's Health Initiative Memory Study (n = 6379), 11 years followup (n = 703), type-2 diabetes RBC membrane (% total FA) PM +ly associated with type-2 diabetes [64] Men and women (n = 358), aged 30-65 at coronary artery disease risk NEFA (μmol L −1 ) P M +ly association with NAFLD but not with atherosclerosis PM, palmitoleic acid; FFA, free fatty acids; TG, triacylglycerol; RBC, red blood cells; MetS, metabolic syndrome; CHD, coronary heart disease; NAFLD, nonalcoholic fatty liver disease, NASH, non-alcoholic steatohepatitis.…”
Section: Referencementioning
confidence: 99%
“…High levels of plasma palmitoleic acid have been described as a marker of MetS and liver fat accumulation [64,65,84,85] (Table 3). Puri et al [85] observed that plasma palmitoleic acid levels in patients with liver disease increased according to the grade of damage, with higher levels in patients with nonalcoholic steatohepatitis than in those with NAFLD [85] (Table 3).…”
Section: Nafldmentioning
confidence: 99%
“…Previous studies also indicate that visfatin has an important enzymatic role in De Novo Lipogenesis (DNL) (11,27), which is known to be increased in NAFLD (29,30), yet hepatic and adipose tissue DNL have opposing effects on the prognosis of NAFLD. Hepatic DNL is positively correlated yet adipose tissue DNL is negatively correlated with fatty liver (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…So, FAEEs are sufficient but not necessary for pancreatic injury. Given that free fatty acids are significantly increased in NAFPD/NASH, it is plausible that they may also mediate the pancreatotoxic effects of EE [13, [106][107][108][109].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, it is known that healthy subjects not exposed to exogenous ethanol have endogenous trace of FAEEs in body fluids [103,104]. As the two substrates required for FAEEs biosynthesis, ethanol [68][77] [105] and free fatty acids [13, [106][107][108][109], are significantly elevated in NASH/NAFPD body fluids, it is quite possible they are formed in toxic amounts in the pancreas and oro-gastrointestinal tract.…”
Section: Endogenous Production Of Fatty Acid Ethyl Esters (Faee)mentioning
confidence: 99%